1992
DOI: 10.1007/bf01709238
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory work imposed by continuous positive airway pressure (CPAP) machines: the effect of CPAP level and endotracheal tube size

Abstract: Inspiratory work imposed by Continuous Positive Airway Pressure (CPAP) machines has been a matter of concern. The imposed inspiratory work of CPAP machine circuits (Wcir) and the effect of the total breathing apparatus with endotracheal tube (ETT) and connector included in the circuit (Wapp), were measured in three continuous flow (CF) and various configurations of three demand flow (DF) CPAP machines. The performance was assessed at 0, 5, 10 and 15 cmH2O CPAP using a Michigan Instruments Test Lung Model 1600,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Most experimental and clinical studies designed to test trigger sensitivity have focused on comparisons among the different available systems for a given ventilator. Continuous positive airway pressure systems have been compared on different ventilators [16,17,18,19,20], whereas only a few studies evaluating trigger performance of ICU ventilators are currently available [10]. Recently, Williams et al reported a bench test study in which the performance of seven ventilators, set in PSV mode, were tested under different conditions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental and clinical studies designed to test trigger sensitivity have focused on comparisons among the different available systems for a given ventilator. Continuous positive airway pressure systems have been compared on different ventilators [16,17,18,19,20], whereas only a few studies evaluating trigger performance of ICU ventilators are currently available [10]. Recently, Williams et al reported a bench test study in which the performance of seven ventilators, set in PSV mode, were tested under different conditions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en la lesión pulmonar aguda/síndrome de dificultad respiratoria aguda, el área de superficie disponible para el intercambio de gases se reduce significativamente, aquí, la presión positiva de la vía aérea sola puede ser inadecuada para lograr la eliminación necesaria de CO2 sin producir un trabajo respiratorio excesivo. A diferencia de la presión positiva continua de la vía aérea (CPAP), el APRV interrumpe brevemente la presión de la vía aérea para complementar la ventilación espontánea por minuto y evitar la acumulación de CO2 [11], con esto se disminuye el poder mecánico pulmonar. El PM se relaciona directamente con el daño a nivel alveolar secundario al uso de ventilación mecánica invasiva; Gattinoni et al, describe que el PM aumenta de manera exponencial con volúmenes tidales elevados, aumentos en la frecuencia respiratoria y en la presión de conducción de la vía aérea; el uso del APRV busca disminuir estas variables al mantener los alveolos abiertos y con mínimo movimiento [12].…”
Section: Fisiología Respiratoria En Un Paciente En Aprvunclassified
“…Several triggering strategies may be employed to improve patient-ventilator synchrony. A number of studies have compared pressure triggering (PT) and flow triggering (FT) during CPAP, [70][71][72][73][74][75] whereas a smaller number have examined these sensing mechanisms during SIMV, 22,76 assist control ventilation, 39 and pressure support ventilation. 39,40,77,78 The majority of these studies found a reduction in the work of breathing with FT when compared to PT, though this may not be the case when PT sensitivity is set at 0.5 or 1.0 cmH 2 O during PSV.…”
Section: Trigger Dyssynchronymentioning
confidence: 99%